An empirical study on the green skill development programme and its inclusiveness in green industries for effective green marketing and sustainable development: key success factors and challenges - S , Mallika D.; Jebasingh, D. Raja (BOHR International Journal of Finance and Market Research, 2023)
India is a young, human-resources-rich nation. With regard to our country’s economic growth, India continues to lag behind due to various issues such as homelessness, unemployment, analphabetism, infrastructure for medical care, etc. Youth play a crucial role in the country’s economic growth. The Green Skill Development Programme (GSDP) of the Ministry of Environment, Forests, and Climate Change (MoEF and CC) is an environmental and forestry skills development initiative to encourage young people in India to procure employment and/or selfemployment. The system aims to develop long-term workers who are technically skilled and committed to sustainability. In June 2017, the GSDP pilot project was launched. In the current situation, it has been discovered that the majority of young people being trained face a severe labor shortage due to a lack of skills and technical knowledge. Most of them do not know what is happening with today’s technology. Attempts to supply sustainability skills are made through the GSDP, which are also known as “green skills.” These are the skill sets, expertise, values, and attitudes that the workers need to develop and foster sustainable social, ecological, and economic conditions in business, industry, and the community. Such companies favor workers who possess green skills to achieve their mission. In this study, an effort is made to define the primary green skills sought by the green sector, determine how successful the GSDPs have been, and identify the foremost challenges experienced by the youth in participating in the government-sponsored GSDPs.